El Estado federal y la preservación y manejo de áreas de singular importancia ambiental - Cuminetti, Simón (2013)
As regards to environmental matters, section 14 of the National Constitution\nstates that ?the authorities will provide (?), to the rational use of natural resources,\nthe preservation of the natural and cultural heritage, and biological diversity, and to\nenvironmental education and information?. The creation, management, protection and\ngradual expansion of the Sistema Federal de Áreas Naturales Protegidas? (Natural\nProtected Areas Federal System) represents a concrete answer, from federal authorities\nto the constitutional order in question.\nThe environmental management categories that make up the Sistema Federal de Áreas\nNaturales Protegidas are: Parque Nacional (National Park), Monumento Natural\n(Natural Monument), Reserva Nacional (National Reserve) and Red de Reservas\nNaturales (the Network of Nature Reserves) ?Reserva Natural Estricta (Strict Nature Reserve), Reserva Natural Silvestre (Wild Nature Reserve) and Reserva Natural\nEducativa (Educational Nature Reserve)?.\nTwo new environmental management categories have recently been added to the system:\nReserva Natural Militar (Military Nature Reserve) and Parque Interjurisdiccional\nMarino-Costero (Inter-jurisdictional Coastal Marine Park).\nThe main administrative-legal aspects that characterize each of the environmental management\ncategories, that make up the Sistema Federal de Áreas Naturales Protegidas,\nare analyzed in the present study.